2022
DOI: 10.3390/cells11213394
|View full text |Cite
|
Sign up to set email alerts
|

Whole Transcriptome Sequencing Reveals Cancer-Related, Prognostically Significant Transcripts and Tumor-Infiltrating Immunocytes in Mantle Cell Lymphoma

Abstract: Mantle cell lymphoma (MCL) is an aggressive B-cell non-Hodgkin lymphoma (NHL) subtype characterized by overexpression of CCND1 and SOX11 genes. It is generally associated with clinically poor outcomes despite recent improvements in therapeutic approaches. The genes associated with the development and prognosis of MCL are still largely unknown. Through whole transcriptome sequencing, we identified mRNAs, lncRNAs, and alternative transcripts differentially expressed in MCL cases compared with reactive tonsil B-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 101 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Among the top 20 dysregulated lncRNAs, low expression of FTX was associated with poor OS. Based on this study lncRNAs play a role in MCL pathogenesis mostly via epidermal growth factor (EGF) receptor, Wnt and mammalian target of rapamycin (mTOR) signalling pathways 58 . Among lncRNAs with a diagnostic value, lncRNAs GATA6‐AS 59 and MORT 61 were downregulated, and lncRNAs MANCR 64 and LINK‐A 65 were upregulated.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Among the top 20 dysregulated lncRNAs, low expression of FTX was associated with poor OS. Based on this study lncRNAs play a role in MCL pathogenesis mostly via epidermal growth factor (EGF) receptor, Wnt and mammalian target of rapamycin (mTOR) signalling pathways 58 . Among lncRNAs with a diagnostic value, lncRNAs GATA6‐AS 59 and MORT 61 were downregulated, and lncRNAs MANCR 64 and LINK‐A 65 were upregulated.…”
Section: Resultsmentioning
confidence: 97%
“…Eight studies assessed the role of lncRNAs in patients with MCL 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 (Table 4 ). A WTS study demonstrated that 1067 lncRNAs were upregulated and 989 lncRNAs were downregulated in patients with MCL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations